MYCN in human development and diseases - Nishio, Yosuke; Kato, Kohji; Oishi, Hisashi; Takahashi, Yoshiyuki; Saitoh, Shinji (Frontiers in Oncology, 2024)
Somatic mutations in MYCN have been identified across various tumors, playing pivotal roles in tumorigenesis, tumor progression, and unfavorable prognoses. Despite its established notoriety as an oncogenic driver, there is a growing interest in exploring the involvement of MYCN in human development. While MYCN variants have traditionally been associated with Feingold syndrome type 1, recent discoveries highlight gain-of-function variants, specifically p.(Thr58Met) and p.(Pro60Leu), as the cause for megalencephalypolydactyly syndrome. The elucidation of cellular and murine analytical data from both lossof-function (Feingold syndrome model) and gain-of-function models (megalencephalypolydactyly syndrome model) is significantly contributing to a comprehensive understanding of the physiological role of MYCN in human development and pathogenesis. This review discusses the MYCN's functional implications for human development by reviewing the clinical characteristics of these distinct syndromes, Feingold syndrome, and megalencephaly-polydactyly syndrome, providing valuable insights into the understanding of pathophysiological backgrounds of other syndromes associated with the MYCN pathway and the overall comprehension of MYCN's role in human development.